1978
DOI: 10.1242/dev.46.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Studies on dwarf larvae developed from isolated blastomeres of the starfish,Asterina pectinifera

Abstract: Not only a whole denuded egg, but also blastomeres isolated from 2-, 4- and 8-cell starfish embryos developed into morphologically normal, but dwarf bipinnariae, the sizes of which were roughly proportionate to that of the respective original blastomeres. Some of the blastomeres isolated from the 16-cell stage were also capable of developing into the larval stage. All isolated blastomeres divided in good synchrony with the control embryos. Blastulae of all groups gastrulated within quite a short range of time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…Taken together these results suggest that the vegetal portion of the embryo is necessary and sufficient for gut formation and establishment of the DV axis, although vegetal blastomeres isolated at the 8-cell stage establish a DV axis with considerable delay. It is worth noting that these results contradict Dan-Sohkawa and Satoh (Dan-Sohkawa and Satoh, 1978), who showed all blastomeres isolated at the 8 cell stage form gastrulae in P. pectinifera , but in agreement with Maruyama and Shinoda (Maruyama and Shinoda, 1990) who showed only the vegetal blastomeres form gastrulae in that same species. Interestingly, Maruyama and Shinoda find that all isolated blastomeres at the 2 and 4 cells stage, and all of the vegetal blastomeres isolated at the 8-cell stage form bipinnaria, although they do not discuss the timing of these events.…”
Section: Resultssupporting
confidence: 44%
See 1 more Smart Citation
“…Taken together these results suggest that the vegetal portion of the embryo is necessary and sufficient for gut formation and establishment of the DV axis, although vegetal blastomeres isolated at the 8-cell stage establish a DV axis with considerable delay. It is worth noting that these results contradict Dan-Sohkawa and Satoh (Dan-Sohkawa and Satoh, 1978), who showed all blastomeres isolated at the 8 cell stage form gastrulae in P. pectinifera , but in agreement with Maruyama and Shinoda (Maruyama and Shinoda, 1990) who showed only the vegetal blastomeres form gastrulae in that same species. Interestingly, Maruyama and Shinoda find that all isolated blastomeres at the 2 and 4 cells stage, and all of the vegetal blastomeres isolated at the 8-cell stage form bipinnaria, although they do not discuss the timing of these events.…”
Section: Resultssupporting
confidence: 44%
“…Sea star embryos present holoblastic cleavage, with the first and second cleavages both aligned with the animal-vegetal axis and the third cleavage perpendicular to the first two, and dividing animal and vegetal halves of the embryo (Byrne and Barker, 1991; Dan-Sohkawa and Satoh,1978; Kominami, 1983). The animal-vegetal axis is established during oogenesis: the germinal vesicle is asymmetrically positioned in the immature oocyte, predicting both the site of polar body extrusion and the anterior side of the embryo (Kominami, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Komatsu (1972) observed the wrinkled blastula stage of this species collected on the coast of Toyama Bay, Sea of Japan, and she pointed out that the wrinkled blastula stage was inevitable in the normal course of development of this species. The recent report of Dan-Sohkawa and Satoh (1978), however, showed that most of the embryos of this species collected on the coast of Tokyo Bay, Pacific Ocean, did not form wrinkled blastulae. These seemingly contradictory reports indicate at least two possibilities on the wrinkled blastula formation of this species.…”
mentioning
confidence: 78%
“…On the other hand, Dan (1957) and Dan-Sohkawa and Satoh (1978) reported that most of the embryos of this species collected on the coast of Tokyo Bay, Pacific Ocean, did not form wrinkled blastulae. However, these reports did not present any actual percentage of wrinkled blastula formation.…”
Section: Discussionmentioning
confidence: 99%
“…Sea star embryos present holoblastic cleavage, with the first and second cleavages both aligned with the animal-vegetal axis and the third cleavage perpendicular to the first two, and dividing animal and vegetal halves of the embryo [ 15 , 18 , 19 ]. The animal-vegetal axis is established during oogenesis: the germinal vesicle is asymmetrically positioned in the immature oocyte, predicting both the site of polar body extrusion and the anterior side of the embryo [ 15 ].…”
Section: Introductionmentioning
confidence: 99%